FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN MP - ASI DINI DI DESA 2 DAYO WILAYAH KERJA PUSKESMAS TANDUN II KABUPATEN ROKAN HULU TAHUN 2013 - Aldriana, Nana (Jurnal Martenity and Neonatal, 2015)
Based on data from Demographic and Health Survey (2003) most of the babies are getting food beside breast feeding from an early age, 36% of infants aged less than 2 months receive complementary feeding as solid foods or creamed. MP-ASI is a food that is given the baby together with the milk. MP-ASI is given after 6 months of age because the reserves of vitamins and minerals in the body obtained during the baby in the womb begins to decrease so that the necessary additional food other than breast milk. The goal is to determine the factors associated with giving early ekstra food beside breast feeding at 2 Dayo village Puskesmas Tandun II Rokan Hulu. This type of research is quantitative analytic with cross sectional design. The study population and sample were 43 people and taken by total sampling. The result of this study shows most of the mother gave early food beside breast feeding to their babies (52%). The conclusion is that there is a relationship between education, work and knowledge with giving early food beside breast feeding. It is hoped that health professionals can always provide the best service to mothers and for mothers who work to keep giving breast milk to her baby